PENGARUH KOMISARIS INDEPENDEN, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Qomariah, Naila Nazatul; Mubarok, Abdullah (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to examine the influence of independent commissioners, institutional ownership, and company size on tax avoidance. The objects in this study are consumer non-cyclicals sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This research method is quantitative research. The population in this study is 125 consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX). The sampling method used in this study is purposeful sampling. The data analysis technique used in this study is multiple linear regression and processed using the Eviews Version 12 program. Based on the results of the F test, the independent commissioner variable, institutional ownership, and company size simultaneously or jointly influence the tax avoidance variable. And partially the results of the study show that company size has a significant effect on tax avoidance. While the independent commissioner and institutional ownership hypotheses are rejected on tax avoidance.